Vodcast embedded with physics education technology simulation in learning projectile motion - Celestino-Salcedo, Reina Karen M.; Malayao, Jr., Sotero O.; Salic-Hairulla, Monera A.; Castro, Ellen Jarantilla; Mordeno, Ivy Claire V. (Intelektual Pustaka Media Utama, 2024)
The challenge of creating reliable technology-based resources for science learning is perennial challenge in Philippine education with the limited learning materials accessible to all learners. This study is about the development of vodcast embedded with physics education technology (PhET) simulation that served as a supplementary learning material for grade 9 Science in response to the scarcity of dependable visualization materials. The study employed the developmental research design with analysis-design-development-implementation-evaluation (ADDIE) model as the developmental framework. Vodcast evaluation tool, achievement test questionnaire, and vodcast perception survey questionnaire for students and for teachers were used in the data collection while the Kendall’s W statistic, mean, percentage, and gain score were used in data interpretation. The teacher respondents (N=64) have moderate agreement on the ranking of topic difficulty with Kendall’s W of 0.45. The researcher-made vodcast attained an overall rating of 4.78 from experts which implies that the vodcast can be a very good material for classroom implementation. The developed achievement test has acceptable difficulty and discrimination indices. The implementation stage yielded low normalized gain and can be accounted by unfocused attention during the pandemic. Nevertheless, the vodcasts were found very useful in learning projectile motion as perceived by both students and teacher-observers.